The life and work of Ernesto de Martino : Italian perspectives on apocalypse and rebirth in the modern study of religion - Geisshuesler, Flavio A. (Brill, 2021)
"In The Life and Work of Ernesto de Martino, Flavio A. Geisshuesler offers a comprehensive study of one of Italy's most colorful historians of religions. The book inserts de Martino's dramatic life trajectory within the intellectual climate and the socio-political context of his age in order to offer a fresh perspective on the evolution of the discipline of religious studies during the 20th century. Demonstrating that scholarship on religion was animated by moments of fear of the apocalypse, it brings de Martino's perspective into conversation with Mircea Eliade, Claude Lévi-Strauss, and Clifford Geertz in order to recover an Italian approach that promises to redeem religious studies as a relevant and revitalizing field of research in the contemporary climate of crisis"--